The Role of Teachers in Managing Inclusive Classrooms at SDN Pinang Ranti 05 Pagi - Nudiya, Asa (Literasi Nusantara, 2025)
This study aims to analyze the role of teachers in managing inclusive classrooms at SDN Pinang Ranti 05 Pagi. Inclusive classrooms represent an educational approach that accommodates the needs of all students, including students with special needs (SWN), within a single learning environment. The goal of inclusive education is to provide equal learning opportunities for all students, including those with special needs. The learning provided encompasses not only academic aspects but also emotional development and social life. The presence of teachers in implementing inclusive education plays a crucial role in creating a learning-friendly environment for all students. Teacher training and professional development are essential for enhancing their competence in managing inclusive classrooms. This study employs a qualitative approach using observation, interviews, and document analysis methods. The findings indicate that the success of inclusive classroom management heavily depends on teachers' competencies in understanding students' needs, applying inclusive learning strategies, and establishing effective communication with students, parents, and other support staff. Thus, teachers are required not only to possess pedagogical skills but also sensitivity to the diversity of students. This study provides important implications for inclusive education policies in Indonesia, particularly in improving teacher capacity and providing adequate facilities to support the success of inclusive education.